Effect of Orthodontic Tooth Movement on Gingival Crevicular Fluid Infiltration; a Preliminary Investigation - A. Dannan; MA. Darwish; MN. Sawan (Tehran University of Medical Sciences, 2009)
Objective: The gingival crevicular fluid (GCF) is an inflammatory exudate found in the gingival sulcus. The forces exerted during orthodontic treatment cause distortion of the periodontal ligament (PDL) extra-cellular matrix, resulting in some biological features that can lead to modification of both GCF volume and its components. The present study investigated the effect of orthodontic tooth movements, specifically canine retraction, on the volume of GCF exudate. Materials and Methods: Fourteen upper and lower canines of patients with different Angle classifications were selected for the study. After extraction of the first premolars, the canines were subjected to orthodontic distal retraction. GCF was sampled from mesial and distal gingival crevices of each canine separately at baseline, 1 hour, 7 days, 14 days, 21 days, and 28 days after the application of the orthodontic distal retraction. GCF volume was determined by means of an electronic device. Results: GCF volume at tension sites was slightly greater after 21 and 28 days compared to other observation time points. At pressure sites, GCF volume was slightly greater after 28 days compared to other observation time points. None of the observed differences, however, was statistically significant (P>0.05). Conclusion: Orthodontic tooth movement, namely canine retraction, does not significantly increase the volume of GCF exudate. The slight increase in GCF volume could be due to a slight degree of gingival inflammation.